Mesoscale eddies induce variability in the sea surface temperature gradient in the Kuroshio Extension - Tang, Rui; Yu, Yi; Xi, Jingyuan; Ma, Wentao; Wang, Yuntao (Frontiers in Marine Science, 2022)
The Kuroshio Extension (KE) region is one of the most energetic regions in the global ocean where prominent mesoscale dynamics persistently occur. The spatial distribution and temporal evolution of the sea surface temperature (SST) gradient and mesoscale eddies in the KE are investigated. The SST gradient can be applied for identifying the fronts, and the SST gradient within two times the radii of the eddies is composited to quantify the impact of eddies on frontal activities. Depressed SST gradients are identified for eddies with both polarities, but prominent spatial variance in the SST gradient reveals that a large SST gradient is located to the north of anticyclones and along the south periphery for cyclones. The eddies are further separated into two groups depending on their location relative to the main path of the KE, as the background fields to the north and south of the KE are largely different. The spatial pattern, e.g., monopole and dipole features, and temporal variation in the SST gradient are fully studied over the lifespans of eddies. The results show that most eddies can significantly weaken the internal SST gradient and induce the horizontal redistribution of the SST gradient in surrounding regions. Cyclonic eddies north of the KE elevate the fronts along the periphery of eddies. The temporal variability in the SST gradient is prominent and largely varies for each group of eddies. This study offers quantitative analyses of the spatial and temporal relationships between eddies and fronts that are important for understanding the mesoscale dynamics in the world’s oceans.